2016
DOI: 10.1017/s1368980016002664
|View full text |Cite
|
Sign up to set email alerts
|

Operationalising the health aspects of sustainable diets: a review

Abstract: Although the sustainability concept is increasingly popular and widely advocated by nutritional and environmental scientists, the journey towards designing sustainable diets for consumers has only just begun. In the context of operationalising the health aspects, diet modelling might be considered the preferred approach since it captures the complexity of the diet as a whole. For the future, we propose SHARP diets: environmentally Sustainable (S), Healthy (H), Affordable (A), Reliable (R) and Preferred from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 78 publications
(256 reference statements)
1
65
1
Order By: Relevance
“…Biesbroek et al, (2017) found in a Dutch cohort (EPIC-NL) that had better adherence to the Dutch dietary guidelines, assessed with DHD15, was associated as well with lower GHG emission [33] but did not investigate individual components of the DHD15. Studies investigating individual components of dietary quality scores [36] were not comparable with our results due to underlying country specific dietary guidelines [37].…”
Section: Discussioncontrasting
confidence: 91%
“…Biesbroek et al, (2017) found in a Dutch cohort (EPIC-NL) that had better adherence to the Dutch dietary guidelines, assessed with DHD15, was associated as well with lower GHG emission [33] but did not investigate individual components of the DHD15. Studies investigating individual components of dietary quality scores [36] were not comparable with our results due to underlying country specific dietary guidelines [37].…”
Section: Discussioncontrasting
confidence: 91%
“…Household food budgets vary across the population, and this needs to be factored in to recommended dietary changes. Through dietary modelling it has been shown that healthy, affordable and low-GHGE diets are feasible at the population level (35)(36)(37)(38)(39)(40)(41)(42)(43) . However, to shift to the types of diets proposed, lower-income groups would need to spend between 18 and 74 % of their total household income on food, while high-income groups would have to spend between only 6 and 10 % to achieve a similar diet (44)(45)(46) .…”
mentioning
confidence: 99%
“…As pointed out in this agenda, while substantial environmental impacts from food occur in the production phase (agriculture, food processing), households influence these impacts through their dietary choices and habits. As a matter of fact, quoting (Mertens et al, 2017), "shifting towards a more sustainable food consumption pattern is an important strategy to mitigate climate change. In the past decade, various studies have optimized environmentally sustainable diets using different methodological approaches.…”
Section: Introductionmentioning
confidence: 99%